Adherent/invasive Escherichia coli (AIEC) isolates from asymptomatic people: new E. coli ST131 O25:H4/H30-Rx virotypes - Edwin Barrios-Villa; Gerardo Cortés-Cortés; Patricia Lozano-Zaraín; Margarita María de la Paz Arenas-Hernández; Claudia Fabiola Martínez de la Peña; Ygnacio Martínez-Laguna; Carmen Torres; Rosa del Carmen Rocha-Gracia (BMC, 2018)
Abstract Background The widespread Escherichia coli clone ST131 implicated in multidrug-resistant infections has been recently reported, the majority belonging to O25:H4 serotype and classified into five main virotypes in accordance with the virulence genes carried. Methods Pathogenicity Islands I and II (PAI-I and PAI-II) were determined using conventional PCR protocols from a set of four E. coli CTXR ST131 O25:H4/H30-Rx strains collected from healthy donors' stool. The virulence genes patterns were also analyzed and compared them with the virotypes reported previously; then adherence, invasion, macrophage survival and biofilm formation assays were evaluated and AIEC pathotype genetic determinants were investigated. Findings Non-reported virulence patterns were found in our isolates, two of them carried satA, papA, papGII genes and the two-remaining isolates carried cnfI, iroN, satA, papA, papGII genes, and none of them belonged to classical ST131 virotypes, suggesting an endemic distribution of virulence genes and two new virotypes. The presence of PAI-I and PAI-II of Uropathogenic E. coli was determined in three of the four strains, furthermore adherence and invasion assays demonstrated higher degrees of attachment/invasion compared with the control strains. We also amplified intI1, insA and insB genes in all four samples. Interpretation The results indicate that these strains own non-reported virotypes suggesting endemic distribution of virulence genes, our four strains also belong to an AIEC pathotype, being this the first report of AIEC in México and the association of AIEC with healthy donors.